Frakturprothesen - Worauf kommt es an?: Leitthema - Kimmeyer, Michael; Hackl, Michael; Lehmann, Lars (Die Unfallchirurgie, 2025)
In cases of complex proximal humeral fractures a fracture prosthesis is an established treatment option. In the geriatric patient population, the use of reverse total shoulder arthroplasty is gaining in relevance. This article focuses on the specific requirements and challenges associated with the application of reverse total shoulder arthroplasty. Decisive for the success are a structured perioperative management, meticulous preoperative planning, thorough patient education and standardized protocols for infection and bleeding prophylaxis. Intraoperatively, emphasis is placed on precise implantation techniques and stable tuberosity fixation, of which the latter is essential for postoperative function. A humeral inclination of 135° has been shown to be associated with better tuberosity healing. Complications, such as scapular notching or instability can be minimized through an accurate surgical technique and optimized implant management. Postoperative care is tailored to the individual, employing either a shoulder abduction brace or an early functional rehabilitation approach. Overall, reverse shoulder arthroplasty provides an effective fracture treatment for geriatric patients, ensuring long-term functional and clinical benefits.
Gesehen am 12.06.2025